2011
DOI: 10.1590/s0036-36342011000400005
|View full text |Cite
|
Sign up to set email alerts
|

Validity of underlying cause of death statistics in Hermosillo, Mexico

Abstract: Objective. This paper assesses the quality of the underlying cause of death (COD) statistics in Hermosillo, Mexico in a random sample of 300 in-hospital adult deaths. Material and Methods. A "gold standard" COD, determined by a systematic review of hospital medical charts, was compared to the COD reported by the vital registry system. Results. Overall agreement between the reviewer and original COD at the ICD-10 chapter block was 69.2%, with a weighted kappa of 0.62. Agreement varied greatly by ICD-10 chapter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…This would suggest a relatively large implied change in the cause specifi c mortality fraction (CSMF). This fi nding is in contrast to studies by Rao et al and Carvalho et al where they report minimal or no misclassifi cation of cerebrovascular diseases in their studies Carvalho et al 2011). The consequences of such misclassifi cation of leading causes of death could be substantial for public health programs since strategies and approaches to prevention are different for each disease category.…”
Section: Discussioncontrasting
confidence: 71%
“…This would suggest a relatively large implied change in the cause specifi c mortality fraction (CSMF). This fi nding is in contrast to studies by Rao et al and Carvalho et al where they report minimal or no misclassifi cation of cerebrovascular diseases in their studies Carvalho et al 2011). The consequences of such misclassifi cation of leading causes of death could be substantial for public health programs since strategies and approaches to prevention are different for each disease category.…”
Section: Discussioncontrasting
confidence: 71%
“…Surprisingly, in our selected studies, ill-defined causes of death were frequently reported even in hospital settings. The policy impact of allocating these non-specific codes to more definitive causes are reported in two studies; 21 , 44 key findings from a meta-analysis of misclassification patterns can be found in the article by Rampatige et al 47 …”
Section: Resultsmentioning
confidence: 99%
“…In Mexico, agreement between death certificates and medical records appears to be moderately high for neoplasia (85% agreement), but not for hypertensive diseases, diabetes, and infections. 6 The 25% difference in mortality estimates for CKD underscores the challenges of assigning causes of death and warrants a more detailed investigation of the potential source of this difference given the increasing importance of the burden of CKD in Mexico. 11,12 This finding also sheds light on the fact that although Mexico's official death registration has been rated with the highest quality based on completeness and coding characteristics, inaccuracy in data processing may be present for certain diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that Mexico's low cancer mortality could be attributable to pitfalls in death certificate coding and attribution of underlying cause of death in national mortality registry used for mortality statistics. 6 We aim to explore death registration inaccuracy by comparing cancer mortality rates from Mexico's official death registry with a death registry from a disease surveillance system that independently processes death certificates.…”
Section: Introductionmentioning
confidence: 99%